Pediatric Boot Camp Series: Infant With Altered Mental Status and Seizure—A Case of Child Abuse - James Metz (Association of American Medical Colleges, 2017)
Introduction Child abuse, also known as nonaccidental trauma (NAT), is an important cause of pediatric morbidity and mortality. The presentation of NAT is often confounded by unclear histories and victims who are unable to provide information. Medical students and trainees may fail to consider NAT as a diagnosis or be unfamiliar with the evaluation process. Methods This curriculum uses simulation, small-group discussion, and didactics to help medical students gain an understanding of presentation of NAT. Using the case of a 2-month-old boy presenting with altered mental status and seizure, participants practice the assessment and management of an acutely ill patient. Small-group discussions facilitate schema building to enhance each participant's ability to recognize and diagnose different diseases that may present as infant seizure and to identify the signs of NAT. Didactics solidify concepts addressed during the simulation and small-group discussions. Results Medical students participating in this course reported that they felt better prepared for their internships and that working through a case with a large differential diagnosis was helpful for their understanding of causes of infant seizures, including abusive head trauma. Discussion This curriculum is unique in that it uses one unifying case to allow participants to demonstrate an understanding of the evaluation and stabilization of a critically ill pediatric patient, develop a broad differential diagnosis for a nonspecific symptom, and prioritize and evaluate possible etiologies through the gathering and interpretation of data. This curriculum may be used independently or in conjunction with other learning activities as part of a pediatric boot camp.